Omeprazole for Refractory Gastroesophageal Reflux Disease during Pregnancy and Lactation - John K Marshall; Alan BR Thomson; David Armstrong (Canadian Journal of Gastroenterology)
Symptomatic gastroesophageal reflux is a common complication of pregnancy and lactation. However, the safety of many effective medical therapies, including oral proton pump inhibitors, has not been well defined. The administration of oral omeprazole to a 41-year-old female during the third trimester of pregnancy, after ranitidine and cisapride failed to control her refractory gastroesophageal reflux, is reported. No adverse fetal effects were apparent, and the patient elected to continue omeprazole therapy (20 mg/day) while breastfeeding. Peak omeprazole concentrations in breast milk (58 nM, 3 h after ingestion) were less than 7% of the peak serum concentration (950 nM at 4 h), indicating minimal secretion. Although omeprazole is a potentially useful therapy for refractory gastroesophageal reflux during pregnancy and lactation, further data are needed to define better its safety and efficacy.